RETRACTED ARTICLE: A comparative pulmonary pharmacokinetic study of budesonide using polymeric nanoparticles targeted to the lungs in treatment of asthma. Issue 1 (1st January 2020) - Ahmad, Niyaz; Ahmad, Rizwan; Almakhamel, Mortaja Zaki; Ansari, Khalid; Amir, Mohd; Ahmad, Wasim; Ali, Abuzer; Ahmad, Farhan Jalees
Abstract: We, the Editors and Publishers of Artificial Cells, Nanomedicine, and Biotechnology have retracted the following article: Niyaz Ahmad, Rizwan Ahmad, Mortaja Zaki Almakhamel, Khalid Ansari, Mohd Amir, Wasim Ahmad, Abuzer Ali & Farhan Jalees Ahmad. (2020). A comparative pulmonary pharmacokinetic study of budesonide using polymeric nanoparticles targeted to the lungs in treatment of asthma. Artificial Cells, Nanomedicine, and Biotechnology, 48:1, 749–762. DOI: 10.1080/21691401.2020.1748640 This article is retracted due to concerns raised regarding the integrity of Figures in the article, including Figures 1, 3, and 10. When asked for an explanation, the authors were unable to provide a satisfactory explanation or the raw data that would support the integrity of their research. Because of this, the Editors agreed the findings of the study are no longer valid and advised for the article to be retracted. The authors do not agree with the retraction. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".